(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Data on diatoms species composition of National Nature Park “Oleshkivski Piski” are given for the first time. The checklist consists of 46 species with 3 of them new to Ukraine, such as Navicula vilaplanii (Lange–Bert. et Sabater) Lange–Bert. et Sabater, Pinnularia sinistra Krammer and Stauroneis obtusa Lagerstedt.